(3efGd GdWGdH aj TQM WhGd GdZQGFHs - (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO Hf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s ((3eMeO Hf fUQ Gddg Hf eMeO s)
(3ChdgG (B:s
(3CMeO Gddg Ydi fYeg Mb MeOg CeG HYO aEfi deG HdZJ GdCed hGdZQV hCOjK Gdfad s
(3BNQgG (B:s
(3ef TQM MOjK GdMLGL Hf jhSa GdKbai (B: (3hGdNWhI HGdVe hGdaJM eG Hjf bOei GdeGTi bGd GHf MWGf EPG bUQJ CSjGafG cGf hUdgG NWGfG Edi CYOGFfG efVGQH s
(3GdfSNI HgG MhGTs
(3hgh cJGH ai TQM GdCdaGX GdZQjHI GdhGbYI ai WhGd GdCMGOjK GdfHhjI hGdBKGQ hbO Ufag HYO cJGH GdfgGjI ai ZQjH GdMOjK hGdCKQ GdfGSN gh GHf CNj GdeUfas
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B272 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B174s
Keywords: (3GddZIs